Putting prevention in their pockets: developing mobile phone-based HIV interventions for black men who have sex with men. - Muessig, Kathryn E; Pike, Emily C; Fowler, Beth; Legrand, Sara; Parsons, Jeffrey T; Bull, Sheana S; Wilson, Patrick A; Wohl, David A; Hightow-Weidman, Lisa B (AIDS patient care and STDs, 2013)
Young black men who have sex with men (MSM) bear a disproportionate burden of HIV. Rapid expansion of mobile technologies, including smartphone applications (apps), provides a unique opportunity for outreach and tailored health messaging. We collected electronic daily journals and conducted surveys and focus groups with 22 black MSM (age 18-30) at three sites in North Carolina to inform the development of a mobile phone-based intervention. Qualitative data was analyzed thematically using NVivo. Half of the sample earned under $11,000 annually. All participants owned smartphones and had unlimited texting and many had unlimited data plans. Phones were integral to participants' lives and were a primary means of Internet access. Communication was primarily through text messaging and Internet (on-line chatting, social networking sites) rather than calls. Apps were used daily for entertainment, information, productivity, and social networking. Half of participants used their phones to find sex partners; over half used phones to find health information. For an HIV-related app, participants requested user-friendly content about test site locators, sexually transmitted diseases, symptom evaluation, drug and alcohol risk, safe sex, sexuality and relationships, gay-friendly health providers, and connection to other gay/HIV-positive men. For young black MSM in this qualitative study, mobile technologies were a widely used, acceptable means for HIV intervention. Future research is needed to measure patterns and preferences of mobile technology use among broader samples.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Cellular Phone; Focus Groups; HIV Infections; Homosexuality, Male; Humans; Internet; Intervention Studies; Male; North Carolina; Primary Prevention; Qualitative Research; Risk-Taking; Safe Sex; Socioeconomic Factors; Text Messaging; Young Adult